'Let's share!' The mediating role of employees' self-determination in the relationship between transformational and shared leadership and perceived knowledge sharing among peers. Issue 4 (August 2019) - Coun, Martine (M.J.H.); Peters, Pascale (C.P.); Blomme, Rob (R.J.)
Abstract: Building on social-exchange and self-determination theory, this study aimed to contribute to the scholarly literature on leadership and knowledge sharing by simultaneously testing how shared and transformational leadership and their interrelatedness may foster employees' perceptions of knowledge sharing behaviour among peers. Additionally, we investigated the mediating role of employees' basic psychological needs satisfaction (in terms of autonomy, competence and relatedness, respectively) as an additional explanatory mechanism to reveal how shared and transformational leadership may foster individuals' perceptions of knowledge sharing behaviour among peers. We employed PLS structural equation modelling to analyse survey data obtained from professionals in an R&D unit of a knowledge-intensive firm. We found shared leadership to be the most important factor enhancing employees' perceptions of knowledge sharing among peers, both directly and indirectly through employees' satisfaction of the need for autonomy. Transformational leadership was found to foster employees' knowledge sharing ultimately, through shared leadership and the need for autonomy satisfaction. We concluded that shared forms of leadership supplemented with transformational leadership on the part of formal leaders are important in contemporary work environments as they can foster employees' perceptions of knowledge sharing among peers and contribute towards employees' self-determination, which ultimately enhances perceptions of knowledge sharing among peers.